The field calculation of the electrical current coil scattered by spiral conductive spherical disk - Резуненко, В. А. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”)
The electromagnetic field of the radial electrical current coil, scattered of the spiral conductive spherical dick is analysed. The method of regularization in the strict formulation for functional summarized equations is used. The method of the integral transformations is applied. The principal part of the summarized equations is isolated and inverted. The effective solvability of the infinite system of the linear algebraic equations of the second kind with the completely continuous operator in the Hilbert space of the numerical sequences is obtained. The effectiveness of the constructed algorithm is confirmed. Some resonance frequencies of the structures are examined.